2023
DOI: 10.1126/sciadv.adg2239
|View full text |Cite
|
Sign up to set email alerts
|

Engineering kinetics of TLR7/8 agonist release from bottlebrush prodrugs enables tumor-focused immune stimulation

Abstract: Imidazoquinolines (IMDs), such as resiquimod (R848), are of great interest as potential cancer immunotherapies because of their ability to activate Toll-like receptor 7 (TLR7) and/or TLR8 on innate immune cells. Nevertheless, intravenous administration of IMDs causes severe immune-related toxicities, and attempts to improve their tissue-selective exposure while minimizing acute systemic inflammation have proven difficult. Here, using a library of R848 “bottlebrush prodrugs” (BPDs) that differ only by their R84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…59–62 A library of “bottlebrush-like” polynorbornene nanostructures covalently linked to polyethylene glycol (PEG) chains was synthesized by modifying the linker chemistry of conjugated resiquimod, a TLR7/8 agonist. 63 Changing the azido- and ester-based linker chemistry that conjugated resiquimod allowed for control over the hydrolytic and esterase degradation kinetics, while maintaining the size and morphology of the structure. Increasing local steric hindrance and the charge of each aryl ester linker by modifying the R groups slowed degradation and increased the release half-life of resiquimod.…”
Section: Transport and Processing Characteristics For Immunomodulator...mentioning
confidence: 99%
See 1 more Smart Citation
“…59–62 A library of “bottlebrush-like” polynorbornene nanostructures covalently linked to polyethylene glycol (PEG) chains was synthesized by modifying the linker chemistry of conjugated resiquimod, a TLR7/8 agonist. 63 Changing the azido- and ester-based linker chemistry that conjugated resiquimod allowed for control over the hydrolytic and esterase degradation kinetics, while maintaining the size and morphology of the structure. Increasing local steric hindrance and the charge of each aryl ester linker by modifying the R groups slowed degradation and increased the release half-life of resiquimod.…”
Section: Transport and Processing Characteristics For Immunomodulator...mentioning
confidence: 99%
“…Increasing local steric hindrance and the charge of each aryl ester linker by modifying the R groups slowed degradation and increased the release half-life of resiquimod. 63 In addition to bulkier chemical groups, steric hindrance can be increased through high-density clustering to protect conjugated cargo and reduce the effects of enzymatic degradation and hydrolysis. This technique has widely been employed using DNA-based structures, including spherical nucleic acids (SNAs), 64–66 DNA origami, 67 and single and double stranded DNA nanostructures.…”
Section: Transport and Processing Characteristics For Immunomodulator...mentioning
confidence: 99%
“…The dense grafting of side chains distinguishes this subclass of macromolecules, known as bottlebrushes (BBs), from other branched or comb polymers due to an unorthodox combination of high molar mass yet low viscosity. This behavior is attributed to steric repulsions between neighboring side chains, which occupy the excluded volume near the backbone and increase the BB persistence length. The BB molecular architecture is inspired by naturally occurring proteoglycans present in biological constructs, such as articular cartilage, where lubrication and impact damping are required. , BB syntheses have progressed rapidly since their introduction, ,, showing promise in applications such as super soft gels/elastomers, drug delivery agents photonic crystals, , energy storage, and advanced nanoscale patterning. Despite recent experimental and theoretical efforts, distinct relationships between BB polymer architecture and material properties are still ongoing due to the many modifiable architectural parameters. These include the chemical composition of the backbone and side chains, the number of backbone atoms between side chains ( n g ), the side chain degree of polymerization ( N sc ), and the backbone degree of polymerization ( N bb ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, OEGMA-11 NPs demonstrated not only superior immune evasion but also significantly high tumor accumulation across three subcutaneous cancer models as well as orthotopic glioblastoma and pancreatic cancer models, which showed the best overall performance in tumor-targeted delivery (Figure B and Table S1). , The strong correlation between tumor accumulation and blood-circulation time revealed immune-evasion-mediated tumor targeting. We further found that the OEGMA-11 NPs showed deep penetration into tumor tissues and maintained relatively high concentrations 21 days post injection, thereby facilitating favorable antitumor efficacy.…”
Section: Introductionmentioning
confidence: 99%